Indoxyl sulphate and kidney disease: Causes, consequences and interventions. Issue 3 (March 2016) - Ellis, Robert J; Small, David M; Vesey, David A; Johnson, David W; Francis, Ross; Vitetta, Luis; Gobe, Glenda C; Morais, Christudas
Abstract: In the last decade, chronic kidney disease (CKD), defined as reduced renal function (glomerular filtration rate (GFR) < 60 mL/min per 1.73 m 2 ) and/or evidence of kidney damage (typically manifested as albuminuria) for at least 3 months, has become one of the fastest‐growing public health concerns worldwide. CKD is characterized by reduced clearance and increased serum accumulation of metabolic waste products (uremic retention solutes). At least 152 uremic retention solutes have been reported. This review focuses on indoxyl sulphate (IS), a protein‐bound, tryptophan‐derived metabolite that is generated by intestinal micro‐organisms (microbiota). Animal studies have demonstrated an association between IS accumulation and increased fibrosis, and oxidative stress. This has been mirrored by in vitro studies, many of which report cytotoxic effects in kidney proximal tubular cells following IS exposure. Clinical studies have associated IS accumulation with deleterious effects, such as kidney functional decline and adverse cardiovascular events, although causality has not been conclusively established. The aims of this review are to: (i) establish factors associated with increased serum accumulation of IS; (ii) report effects of IS accumulation in clinical studies; (iii) critique the reported effects of IS in the kidney, when administered both in vivo and in vitro ; and (iv) summarize both established and hypothetical therapeutic options for reducing serum IS or antagonizing its reported downstream effects in the kidney. Summary at a Glance: Indoxyl sulphate is one of many potential protein bound uremic toxins. This review explores the mechanisms behind elevated indoxyl sulphate levels in renal impairment; the effects this may have on the organism; and methods that may lower these elevated levels.